2020
DOI: 10.4028/www.scientific.net/ddf.405.100
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Fractographic Analysis of CuAlNi Shape Memory Alloy before and after Heat Treatment

Abstract: The paper presents comparison of microstructure and fracture surface morphology of the CuAlNi shape memory alloy (SMA) after different heat treatment procedures. The investigation was performed on samples in as-cast state and heat treated states (solution annealing at temperatures of 850 °C / 60’ / H2O and 920 °C / 60’ / H2O along with tempering at two different temperature 150 °C / 60’ / H2O and 300 °C / 60’ / H2O). The microstructure of the samples was examined by optical (OM) and scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…It is known that CuAlNi shape memory alloys undergo a single transformation (β→β 1 or β→γ 1 ) or a mixed transformation (β→β 1 + γ 1 ), which depends on the alloy's chemical composition [35]. The previous works [36] confirmed that, after heat treatment in CuAlNi microstructure, along with β 1 martensite, γ 1 martensite also appears, while in the casted state, only β 1 martensite exists. This indicates that the different types of martensite affect alloys' cavitation erosion resistance.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is known that CuAlNi shape memory alloys undergo a single transformation (β→β 1 or β→γ 1 ) or a mixed transformation (β→β 1 + γ 1 ), which depends on the alloy's chemical composition [35]. The previous works [36] confirmed that, after heat treatment in CuAlNi microstructure, along with β 1 martensite, γ 1 martensite also appears, while in the casted state, only β 1 martensite exists. This indicates that the different types of martensite affect alloys' cavitation erosion resistance.…”
Section: Resultsmentioning
confidence: 89%
“…The previous work confirmed that, after heat treatment in CuAlNi shape memory alloy, along with β 1 martensite, γ 1 martensite also appears in the microstructure. CuAlNi shape memory alloys undergo a single transformation (β→β 1 or β→γ 1 ) or a mixed transformation (β→β 1 + γ 1 ), which depends on alloys' chemical composition [36]. It can be concluded that the morphology of different types of martensite affects alloys' cavitation erosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanical properties notably decreased after heat treatment, the development of favorable martensite phases produced better damping properties. Two types of martensite can be found in this alloy, β 1′ and γ 1′ , respectively [ 26 ]. Appearance of γ 1′ martensite improves the damping capacity of the alloy due to movement of twin boundaries in the martensite phase and higher hysteresis in comparison to β 1′ martensite [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…After solution annealing, the appearance of the intergranular type of fracture was visible, and after tempering at 300 °C/60′/H 2 O, an almost completely intergranular type of fracture appeared. The degradation of fracture mechanisms, or shift from a transgranular type of fracture to intergranular type after heat treatment, can be explained by the alloy’s high elastic anisotropy [ 28 , 29 ] and large grain size [ 30 ]. Stress level concentration is high at large grain boundaries and nucleation of the cracks appears specifically in these places due to low cohesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation